2001
DOI: 10.1046/j.1469-0705.2001.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of 13q– syndrome in a fetus with holoprosencephaly and thumb agenesis

Abstract: Partial deletion of the long arm of one of the chromosomes 13 is an exceedingly rare condition. We report such a case in a 32-week fetus presenting with polyhydramnios, growth restriction and multiple structural defects including alobar holoprosencephaly, facial abnormalities, clubfoot, clinodactyly and thumb agenesis. Fetal blood sampling revealed a 46,XY, del(13)(q22 --> qter) abnormal male karyotype. Postmortem examination confirmed the prenatal findings and showed other manifestations of the syndrome. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 8 publications
2
14
1
1
Order By: Relevance
“…4,13,30,[38][39][40][41][42][43][44] Thus, analysis of the precise location and size of the deletion is needed to better inform families and physicians about the clinical expectations and survival in patients with a 13q deletion.…”
mentioning
confidence: 99%
“…4,13,30,[38][39][40][41][42][43][44] Thus, analysis of the precise location and size of the deletion is needed to better inform families and physicians about the clinical expectations and survival in patients with a 13q deletion.…”
mentioning
confidence: 99%
“…We next extended our CGHa analysis to patients who had been reported as having 13q-syndrome which involves various partial deletions in the q22-qter region (Luo et al, 2000;Gutierrez et al, 2001;Hewson and Carter, 2002). These patients have a well-defined set of clinical phenotypes, including mental retardation, where the deletion was generally assumed to involve the terminal region of 13q, although somatic cell hybrid studies (Hawthorn and Cowell, 1995) suggested that these were, in fact, subterminal deletions.…”
Section: Resultsmentioning
confidence: 99%
“…There is no specific treatment. Psychomotor retardation, usually moderate to severe, is always present [1][2][3][4][5][6][7][8][9][10][11][12]. The exact life span is unknown; the oldest patient included in the above survey was 8 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The present case falls into the third category as a kind of deletion 13. Deletion of the long arm of chromosome 13 is associated with a wide spectrum of abnormalities, including retinoblastoma, mental and growth retardation, brain malformations, heart defects, distal limb deformities, and digestive, urogenital, and other abnormalities [1][2][3][4][5][6][7][8]. Deletions limited to proximal bands (q32) are characterized mainly by growth retardation but no major deformities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation